Seroprevalence of COVID-19 infection in a rural district of Tamil Nadu: A population-based seroepidemiological study - Kannan G; Aruna P; Nithyavikasini N; Kumar Raja M (Asian Journal of Medical Sciences, 2023)
Background: Coronavirus disease 2019 (COVID-19) was a recent global pandemic of the era which posed a great challenge for the health care in terms of preventive, diagnostic and treatment dimensions. The seroprevalence rate of COVID IgG antibodies is very crucial in estimating the susceptibility of a particular area to the viral disease. In our study, we estimated the seroprevalence of COVID-19 in a rural area. Aims and Objectives: We aimed to estimate the seroprevalence of COVID-19 in a rural district of Tamil Nadu, 6 months after the index case. Materials and Methods: We conducted a cross-sectional study of 509 adults aged more than 18 years. From all the seven Taluks, two gram panchayats (administrative cluster of 8–10 villages) were randomly selected followed by one village through convenience. The participants were invited for the study to the community-based study kiosk set up in all the eight villages through village health committees. We collected sociodemographic characteristics and symptoms using a mobile application-based questionnaire, and we tested samples for the presence of IgG antibodies for severe acute respiratory syndrome coronavirus 2 using an electro chemiluminescent immunoassay. We calculated age-gender adjusted and test performance adjusted seroprevalence. Results: The age-and gender-adjusted seroprevalence was 8.5% (95% confidence interval [CI] 6.9–10.8%). The unadjusted seroprevalence among participants with hypertension and diabetes was 16.3% (95% CI: 9.2–25.8) and 10.7% (95% CI: 5.5–18.3), respectively. When we adjusted for the test performance, the seroprevalence was 6.1% (95% CI 4.02–8.17). The study estimated 7 (95% CI 1:4.5–1:9) undetected infected individuals for every reverse transcription polymerase chain reaction confirmed case. Infection fatality rate (IFR) was calculated as 12.38/10,000 infections as on October 22, 2020. History of self-reported symptoms and education were significantly associated with positive status (P<0.05). Conclusion: A significant proportion of the rural population in a district of Tamil Nadu remains susceptible to COVID-19. A higher proportion of susceptible, relatively higher IFR, and a poor tertiary health-care network stress the importance of sustaining the public health measures and promoting early access to the vaccine are crucial to preserving the health of this population. Low population density, good housing, adequate ventilation, limited urbanization combined with public, private, and local health leadership are critical components of curbing future respiratory pandemics.